Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT Widini Mandiri Tangerang - Wifel Brener Gulo; Syarifah Ida Farida (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine the effect of work discipline and work motivation on employee performance at PT Widini Mandiri Tangerang both partially and simultaneously, while in this study using quantitative research methods, with data collection making 50 employees as sample respondents. In this study using several techniques in its testing including validity test, reliability test, classical assumption test, regression test, and t and F hypothesis test. The results of the study showed that in the t test the value of the work discipline variable was 17.378> 1.676 while the work motivation variable was 4.727> 1, then in the t test Ho was rejected and Ha was accepted while in the results of the F hypothesis test on the employee performance variable was 20.401> 3.19 meaning Ho was rejected and Ha was accepted.Keywords: Role of Pricing, Sales Volume Keywords: Work Discipline, Work Motivation, Employee Performance